Given that one of the root of f ( x ) = x 5 + 9 x 4 + 7 x 3 + 1 6 x 2 + 6 x + 7 can be expressed as:
− a − 7 3 b − 3 c 2 − 3 2 b − 3 c
for positive integers a , b and c . Calculate a + b + c + 1 .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
You are an awesome basher sir 🏆!
Log in to reply
Then you must upvote his solution... :P
Neatest Cardano's solution I've seen! VERY NICE!
I will present you 2 methods, first is the long one and second is the short one.
Method-1
Watch a little see a little it gets factorised neatly as follows :
f ( x ) = x 5 + 9 x 4 + 7 x 3 + 1 6 x 2 + 6 x + 7 = ( x 5 + 7 x 3 + 6 x ) + ( 9 x 4 + 1 6 x 2 + 7 )
⇒ f ( x ) = x ( x 2 + 1 ) ( x 2 + 6 ) + ( 9 x 2 + 7 ) ( x 2 + 1 )
⇒ f ( x ) = ( x 2 + 1 ) ( x 3 + 9 x 2 + 6 x + 7 ) = 0
Hence we have two roots of f ( x ) = i , − i
For the rest of the roots, we will solve :
x 3 + 9 x 2 + 6 x + 7 = 0
In the next step of solving the cubic we will first depress the cubic( that is make an appropiate substitution such that co-efficient of x 2 = 0 )
In depressing the cubic a x 3 + b x 2 + c x + d = 0 , we will make the substitution :
x + 3 a b = y
In our cubic we make the substitution x = y − 3 , to get our cubic as :
y 3 + 4 3 = 2 1 y
Now we will make use of the identity :
a 3 + b 3 + y 3 − 3 a b y = ( a + b + y ) ( a 2 + b 2 + y 2 − a b − b y − a y )
Now we will find a , b such that :
a 3 + b 3 = 4 3 , 3 a b = 2 1
Eliminating b from these two equations we have :
a 6 − 4 3 a 3 + 3 4 3 = 0
It is quadratic in a 3 , hence solving for a 3 , we have ;
a 3 = 2 4 3 ± 3 5 3
The real root of cubic in y is given by :
y = − a − b
Since ( a + b + y ) ( a 2 + b 2 + y 2 − a b − a y − b y ) = 0
So let a = 3 2 4 3 − 3 5 3 , remember choice of a is arbitary.
Hence b = 7 3 4 3 − 3 5 3 2
Putting these values we have :
y = − 3 2 4 3 − 3 5 3 − 7 3 4 3 − 3 5 3 2
Finally we have :
x = − 3 − 3 2 4 3 − 3 5 3 − 7 3 4 3 − 3 5 3 2
⇒ a = 3 , b = 4 3 , c = 5 3
Method 2
Put the equation into wolfram-alpha and press OK , and yes you got it.
I believe question poser has solved this question by this alternate way since as soon as I press OK , it returns me exactly the same closed form as he has posed in this problem.
I appreciate your 2 n d approach, really elegant 😱 :p !
This problem is underrated because of the fact that most people tend to use method-2.
ROFL!!!!! @Parth Lohomi is that true? xD
Problem Loading...
Note Loading...
Set Loading...
It is given that f ( x ) = x 5 + 9 x 4 + 7 x 3 + 1 6 x 2 + 6 x + 7 . By trial and error, we have:
\(\begin{array} {} f(\sqrt{-1}) & = f(i) & =i+9-7i-16+6i+7 & = 0 \\ f(-\sqrt{-1}) & = f(-i) & =-i+9+7i-16-6i+7 & = 0 \end{array} \)
⇒ ( x − i ) ( x + i ) = x 2 + 1 is a factor of f ( x ) and f ( x ) = ( x 2 + 1 ) ( x 3 + 9 x 2 + 6 x + 7 ) .
Therefore the real root must come from x 3 + 9 x 2 + 6 x + 7 = 0 , which we can solved for using Cardano Formula as follows.
x 3 + 9 x 2 + 6 x + 7 = 0 ⇒ ( x + 3 ) 3 − 2 1 ( x + 3 ) + 4 3 = 0
Let x + 3 = u 3 + v 3 and 3 u v − 2 1 = 0 then
x 3 + 9 x 2 + 6 x + 7 = u 3 + v 3 + 3 u v ( u + v ) − 2 1 ( u + v ) + 4 3 = u 3 + v 3 + ( 3 u v − 2 1 ) ( u + v ) + 4 3 = u 3 + v 3 + 4 3 = 0
⇒ { u 3 + v 3 = − 4 3 u 3 v 3 = 7 3 = 3 4 3 ⇒ u 3 and v 3 are roots of z 2 + 4 3 z + 3 4 3 = 0
⇒ ⎩ ⎪ ⎪ ⎨ ⎪ ⎪ ⎧ u 3 = 2 − 4 3 + 4 3 2 − 4 ( 3 4 3 ) = − 2 4 3 − 3 5 3 v 3 = − 2 4 3 + 3 5 3 = − 2 ( 4 3 − 3 5 3 ) 4 3 2 − 9 ( 5 3 ) = − 4 3 − 3 5 3 6 8 6
⇒ ⎩ ⎪ ⎪ ⎨ ⎪ ⎪ ⎧ u = − 3 2 4 3 − 3 5 3 v = − 7 3 4 3 − 3 5 3 2
⇒ x = − 3 + v + u = − 3 − 7 3 4 3 − 3 5 3 2 − 3 2 4 3 − 3 5 3
⇒ a + b + c + 1 = 3 + 4 3 + 5 3 + 1 = 1 0 0